Gender and innovation through an intersectional lens: Re‐imagining academic entrepreneurship in the United States. Issue 3 (2nd February 2022) - Mickey, Ethel L.; Smith‐Doerr, Laurel
Abstract: How to study inequality in innovation? Often, the focus has been gender gaps in patenting. Yet much is missing from our understanding of gendered inequality in innovation with this focus. This review discusses how gender and innovation are intertwined in durable academic inequalities and have implications for who is served by innovation. It summarizes research on gender and race gaps in academic entrepreneurship (including patenting), reasons for those longstanding inequities, and concludes with discussing why innovation gaps matter, including the need to think critically about academic commercialization. And while literature exists on gender gaps in academic entrepreneurship and race gaps in patenting, intersectional analyses of innovation are missing. Black feminist theorists have taught us that gender and race are overlapping and inseparable systems of oppression. We cannot accurately understand inequality in innovation without intersectionality, so this is a serious gap in current research. Intersectional research on gender and innovation is needed across epistemic approaches and methods. From understanding discrimination in academic entrepreneurship to bringing together critical analyses of racial capitalism and academic capitalism, there is much work to do.